2017
DOI: 10.1515/ijame-2017-0009
|View full text |Cite
|
Sign up to set email alerts
|

Unsteady MHD Heat Transfer in Couette Flow of Water at 4°C in a Rotating System with Ramped Temperature via Finite Element Method

Abstract: An unsteady magnetohydromagnetic natural convection on the Couette flow of electrically conducting water at 4 0 C (Pr = 11.40) in a rotating system has been considered. A Finite Element Method (FEM) was employed to find the numerical solutions of the dimensionless governing coupled boundary layer partial differential equations. The primary velocity, secondary velocity and temperature of water at 4 o C as well as shear stresses and rate of heat transfer have been obtained for both ramped temperature and isother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Moreover, increasing time and the Hartmann number reduces the longitudinal velocity. Reddy et al [6] used the finite element technique to investigate the unsteady MHD rotating Couette flow of 4℃-water with ramped wall temperature. The finding from this study revealed that the fluid velocity increases when the Grashof number decreases, and is reduced whenever there are increases in Prandtl number and magnetic field parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, increasing time and the Hartmann number reduces the longitudinal velocity. Reddy et al [6] used the finite element technique to investigate the unsteady MHD rotating Couette flow of 4℃-water with ramped wall temperature. The finding from this study revealed that the fluid velocity increases when the Grashof number decreases, and is reduced whenever there are increases in Prandtl number and magnetic field parameter.…”
Section: Introductionmentioning
confidence: 99%
“…The entropy generation and temperature dependent heat source effects on MHD Couette flow with permeable base in the presence of radiation and viscous dissipation was studied by Sukumar and Varma (2016). Reddy et al (2017) investigated unsteady MHD heat transfer in Couette flow of water at 4 O C in a rotating system with ramped temperature. Ajibade and Bichi (2019) examined natural convection Couette flow through a vertical porous channel due to combined effects of thermal radiation and variable fluid properties.…”
Section: Introductionmentioning
confidence: 99%